Funding inclusive education for equity and social justice in South African schools - Tsediso Michael Makoelle; Valeriya Burmistrova (South African Journal of Education, 2020)
The implementation of inclusive education in South African schools has resulted in more demands being placed on them to make provision for the inclusion of learners with special educational needs in mainstream classrooms. This has brought about substantial changes regarding school financing in order to cater for a diverse learner population. This generic qualitative study conducted through interviews with 9 secondary school principals from formerly disadvantaged and advantaged schools, as well as policy document analysis, investigated the current school financing practices for inclusive education in schools aimed at attaining equity and social justice. During this study data were analysed using inductive content analysis. The findings of the study suggest that although provision has been made in terms of the National Norms and Standards for School Funding policy, schools, especially those in previously disadvantaged communities, are not adequately and suitably resourced to implement inclusive education fully.